FRI0570-PC Audit of uptake in primary care of seasonal and pneumococcal vaccination by rheumatology patients on biologic therapy in north devon. (23rd January 2014) - Bartle, S.; Abusalameh, M.; Kyle, S.; Manhas, R.
Abstract : Background: The BSR (1 ) advises patients should be offered seasonal influenza and pneumococcal vaccines at least two weeks prior to immunosuppression, and seasonal vaccination "in line with national guidelines". UK National Guidelines are unclear on the need for booster pneumococcal vaccinations, and the literature is inconclusive. Seasonal vaccinations are usually given in primary care, with financial incentives for vaccinating vulnerable groups. Objectives: To investigate: 1) were patients vaccinated at least 2 weeks prior to starting treatment? 2) was uptake of annual influenza vaccine in the 2011 campaign in line with national uptake? 3) were there gender, age, condition or biologic agent variations in annual influenza vaccination uptake? 4) What percentage of patients had a pneumococcal booster in the last 5 or 10 years? 5) Did patients recall seasonal vaccination advice during Biologic-therapy counselling? 6) Did patient recall of vaccination accord with GP records? 7) What advice do Peninsula Region Rheumatology teams give their Biologics patients on seasonal vaccination timing and pneumococcal boosters? Methods: During September and October 2012, all patients attending the biologic clinic (n=56)completed a questionnaire about their understanding and uptake of seasonal vaccinations. GP practice managers were asked to confirm if each patient on the biologics database (n=175) had vaccinations pre-therapy, and the 2011 annual influenza vaccine. We asked Lead Consultants at Regional Rheumatology Centres what seasonal vaccinations they recommended for their patients, their timing, and if they recommended a pneumococcal booster. Results: North Devon Biologics Patients' uptake of annual influenza vaccine was similar to the national average (73.7 vs 74%). Uptake was lower in males (68.5%), males under 65's (61.5%), males with Psoriatic Arthritis (63.6%) and in Ankylosing Spondylosis (64.0%). Uptake was higher in over-65's (83.9%) and in Rheumatoid patients (74.1%). Annual vaccination uptake was similar across all classes of biologics. 75% of patients recalled advice given during counselling. Patient recall of vaccination was lower for all groups than GP records. GP-recorded vaccination pre-treatment was good in influenza (72.6%); and for females for pneumococcus (80.4%), but poorer for influenza in males under 65 (57.7%). Significant numbers of patients did not have a pneumococcal vaccine in the last 5 years (53.8% of females and 48.8% of males). Most clinicians in the Peninsula region do not recommend pneumococcal boosters, as per BSR guidance. Conclusions: Younger biologic treated patients, particularly males, have a poorer uptake for both pre-treatment and annual vaccinations, compared to national average. Rheumatologists and Primary care colleagues should focus on this at risk group. Clearer National guidelines would help in this regard. References: BSR Statement on Vaccination in Adult Patients with Rheumatic Diseases http://www.rheumatology.org.uk/includes/documents/cm_docs/2011/b/bsr_vaccination_statement_nov_2011.pdf Disclosure of Interest: None Declared